1964
DOI: 10.1039/tf9646001110
|View full text |Cite
|
Sign up to set email alerts
|

Formation, structure and catalytic activity of evaporated palladium-silver films

Abstract: Palladium-silver alloy films were prepared in vacuum either by slow simultaneous evaporation of the component metals from separate wire sources, or from an alloy wire, on to a hot glass substrate, or alternatively by successive evaporation of layers of the metals which were homogenized by heating. X-ray techniques were used to study the effects of the preparative conditions on the degree of homogeneity produced through the bulk of the films and to determine their compositions over the extended area of the reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1967
1967
1971
1971

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Moss and Thomas reported that prior exposure to hydrogen increased the activity of palladium foils for the batchwise oxidation of carbon monoxide. 2 Modell suggested that palladium-hydrogen alloys decrease the activation energy for the oxidation.3 Changes in the infrared spectra of CO chemisorbed on platinum4 and nickel5 samples, brought about by the the addition of hydrogen, have been reported. However, these separate kinetic and spectral changes were not correlated because each employed different catalyst samples.…”
mentioning
confidence: 99%
“…Moss and Thomas reported that prior exposure to hydrogen increased the activity of palladium foils for the batchwise oxidation of carbon monoxide. 2 Modell suggested that palladium-hydrogen alloys decrease the activation energy for the oxidation.3 Changes in the infrared spectra of CO chemisorbed on platinum4 and nickel5 samples, brought about by the the addition of hydrogen, have been reported. However, these separate kinetic and spectral changes were not correlated because each employed different catalyst samples.…”
mentioning
confidence: 99%
“…Clearly surface cleanliness can be improved directly by increasing pumping speed. Moss et al (1970) have been successful in preparing Pd-Ag alloy films in this way. In the present work pumping speed is limited by the 2.25 inch bore bakeable all-metal cock, the presence of which is necessary for gas-handling in planned adsorption work.…”
Section: Discussionmentioning
confidence: 99%
“…Phase separation, which may occur at clean surfaces because rapid atom migration can permit approach there to the thermodynamically more stable two-phase condition, proves to be more difficult to establish experimentally. LEED has failed to demonstrate such an effect (Ertl and Kiippers 1971) but this technique may not be well-suited to yielding a firm decision for the copper-nickel system (Mozer et al 1968). The existence of the (related) clustering of nickel atoms, however, appears well established and, while debate continues as to its magnitude for variously prepared alloy samples (Seib and Spicer 1970), results to date suggest that it may be at least a contributory reason for the lack of success in relating adsorptive and catalytic activity of copper-nickel alloys to their electronic structure (Dowden 1970, McMahon et al 1971).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation